IMPLEMENTASI STANDAR PELAYANAN PUBLIK OLEH PERUM BULOG LAHAT DALAM PROGRAM OPERASI PASAR - Seftyani, Resty; Austin, Trecy; Trecy, Austin (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2025)
This study aims to analyze the implementation of public service standards by Perum BULOG Lahat in conducting the market operation program, identify supporting and inhibiting factors, and assess its impact on public satisfaction and food price stability. This research employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The results indicate that the market operation program implemented by Perum BULOG Lahat complies with the principles of public service as regulated in Law No. 25 of 2009, including transparency, clarity of procedures, timeliness, and affordability. Supporting factors include inter-agency coordination, central government policy support, and community participation, while inhibiting factors consist of limited stock, uneven distribution, and insufficient field personnel. This study recommends enhancing logistics capacity, ensuring equitable distribution, increasing human resources, strengthening coordination, and utilizing information technology to optimize market operation services.